2022
DOI: 10.1111/jipb.13283
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B1 THIAMIN REQUIRING1 synthase mediates the maintenance of chloroplast function by regulating sugar and fatty acid metabolism in rice

Abstract: Vitamin B1 (VB1), including thiamin, thiamin monophosphate (TMP), and thiamin pyrophosphate (TPP), is an essential micronutrient for all living organisms. Nevertheless, the precise function of VB1 in rice remains unclear. Here, we described a VB1 auxotrophic mutant, chlorotic lethal seedling (cles) from the mutation of OsTH1, which displayed collapsed chloroplast membrane system and decreased pigment content. OsTH1 encoded a phosphomethylpyrimidine kinase/thiamin‐phosphate pyrophosphorylase, and was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 74 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…To further test the hypothesis that changes in VB 1 titre in rice contribute to the difference of larval weight, we measured the body weight of SSB caterpillars fed on overexpression ( OxTH1 Nip ) and knockout ( th1 ) rice (ZH11 background) (Supporting Information: Figure ) (Nie et al, 2022) for 7 days. The mean body weight of SSB larvae fed on OxTH1 Nip plants was significantly higher than on WT plants (Figure 3h).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further test the hypothesis that changes in VB 1 titre in rice contribute to the difference of larval weight, we measured the body weight of SSB caterpillars fed on overexpression ( OxTH1 Nip ) and knockout ( th1 ) rice (ZH11 background) (Supporting Information: Figure ) (Nie et al, 2022) for 7 days. The mean body weight of SSB larvae fed on OxTH1 Nip plants was significantly higher than on WT plants (Figure 3h).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the VB 1 ‐dificient rice line negatively affected SSB caterpillars which may indicate a nutrition‐based effect (Figure 3h). Previous studies have shown that a decrease in VB 1 content can lead to a reduction in sugars in rice (Nie et al, 2022) which could contribute to differences in the energy available in the two subspecies. However, when we only deleted VB 1 in artificial diets but maintained sugar levels, effects on larval growth persisted (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). In the plastid, HMP-P is phosphorylated into HMP-PP by the action of the bifunctional HMP-P kinase/TMP synthase (TH1) which subsequently condenses HMP-PP and HET-P to form thiamin monophosphate (TMP) 3 , 10 (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the thiazole moiety (HET-P) is mediated by 4-methyl-5-b-hydroxyethylthiazole phosphate (HET-P) synthase (THI1) 8 , 9 , the substrates of this reaction are nicotinamide adenine dinucleotide (NAD) and glycine 27 . TH1 (HMP-P kinase/thiamin monophosphate (TMP) pyrophosphorylase) phosphorylates HMP-P to HMP-PP and also condenses HMP-PP and HET-P to form TMP 3 , 10 . TH2 dephosphorylates TMP 5 , 11 , 12 which is then pyrophosphorylated to TDP by TDP kinases (TDPK s ) 13 .…”
Section: Introductionmentioning
confidence: 99%